Giant Cell Angiofibroma in Unusual Localization: A Case Report. (18th April 2012) - Pala, Emel Ebru; Beyhan, Rafet; Bayol, Umit; Cumurcu, Suheyla; Kucuk, Ulku
Abstract : Giant cell angiofibroma (GCA) was initially described as a potentially recurrent tumor in the orbit of adults. However, it is now recognized that it can also present in other locations. The morphological hallmark is a richly vascularized patternless spindle cell proliferation containing pseudovascular spaces and floret like multinucleate giant cells. Our case was a 32-years-old female complaining of painless solitary nodule arising on the occipital region of the scalp, which was diagnosed as giant cell angiofibroma. We report the case because of its extremely rare localization.